Oxidative Stress Stimulates Autophagic Flux During Ischemia/Reperfusion - Hariharan, Nirmala (Mary Ann Liebert, Inc., 2011)
Autophagy is a bulk degradation process in which cytosolic proteins and organelles are degraded through lysosomes. To evaluate autophagic flux in cardiac myocytes, we generated adenovirus and cardiac-specific transgenic mice harboring tandem fluorescent mRFP-GFP-LC3. Starvation significantly increased the number of mRFP-GFP-LC3 dots representing both autophagosomes and autolysosomes per cell, suggesting that autophagic flux is increased in cardiac myocytes. H(2)O(2) significantly increased autophagic flux, which was attenuated in the presence of N-2-mercaptopropionyl glycine (MPG), an antioxidant, suggesting that oxidative stress stimulates autophagy in cardiac myocytes. Myocardial ischemia/reperfusion (I/R) increased both autophagosomes and autolysosomes, thereby increasing autophagic flux. Treatment with MPG attenuated I/R-induced increases in oxidative stress, autophagic flux, and Beclin-1 expression, accompanied by a decrease in the size of myocardial infarction (MI)/area at risk (AAR), suggesting that oxidative stress plays an important role in mediating autophagy and myocardial injury during I/R. MI/AAR after I/R was significantly reduced in beclin1(+/−) mice, whereas beclin1(+/−) mice treated with MPG exhibited no additional reduction in the size of MI/AAR after I/R. These results suggest that oxidative stress plays an important role in mediating autophagy during I/R, and that activation of autophagy through oxidative stress mediates myocardial injury in response to I/R in the mouse heart. Antioxid. Redox Signal. 14, 2179–2190.